Prevalence of metchillin: resistant staphylococcus areus in student of higher education - Rodrigues, Francisco (2019)
Introduction: S aureus is a bacterium that is part of the normal flora of many Human Beings, and in its most aggressive variant (MRSA) it can constitute a potential risk for the bearer and the People of their relationship. Objetive: To evaluate the prevalence rate of S aureus and MRSA; assess the main risk factors; evaluate the students' knowledge about the bacterium. Methods: Nasal zaragotoa harvest, with posterior laboratory analysis for bacterial identification and questionnaire. Results: In our study we had 35.23% positive cases for S aureus. In the MRSA prevalence analysis we have 5.7% of positive cases. We found a higher prevalence in the men, with 41.7% positive cases, compared with the women (30.8%). Concerning the MRSA incidence, this is higher in women (5.8%) than in men (5.6%). We can also see that the traineeship has an important role in the contamination. Conclusion: We concluded a high percentage of S aureus carriers and an expected percentage of MRSA carriers.